MTA1 drives malignant progression and bone metastasis in prostate cancer. Issue 9 (14th August 2018) - Kumar, Avinash; Dhar, Swati; Campanelli, Gisella; Butt, Nasir A.; Schallheim, Jason M.; Gomez, Christian R.; Levenson, Anait S.
Abstract : Prostate cancer often metastasizes to the bone, leading to morbidity and mortality. While metastasis‐associated protein 1 (MTA1) is highly overexpressed in metastatic tumors and bone metastatic lesions, its exact role in the development of metastasis is unknown. Here, we report the role of MTA1 in prostate cancer progression and bone metastasis in vitro and in vivo . We found that MTA1 silencing diminished formation of bone metastases and impaired tumor growth in intracardiac and subcutaneous prostate cancer xenografts, respectively. This was attributed to reduced colony formation, invasion, and migration capabilities of MTA1 knockdown cells. Mechanistic studies revealed that MTA1 silencing led to a significant decrease in the expression of cathepsin B (CTSB), a cysteine protease critical for bone metastasis, with an expected increase in the levels of E‐cadherin in both cells and xenograft tumors. Moreover, meta‐analysis of clinical samples indicated a positive correlation between MTA1 and CTSB. Together, these results demonstrate the critical role of MTA1 as an upstream regulator of CTSB‐mediated events associated with cell invasiveness and raise the possibility that targeting MTA1/CTSB signaling in the tumor may prevent the development of bone metastasis in prostate cancer. Abstract : MTA1 is highly overexpressed in metastatic tumors and bone metastatic lesions in human prostate cancer. Our data revealed critical mechanistic role of MTA1 as an upstream regulator of CTSB‐mediated events associated with tumor progression and formation of bone metastasis. MTA1/CTSB axis might represent a novel therapeutic target for prevention of bone metastasis in prostate cancer.